Pengaruh Strategi Metakognisi Terhadap Hasil Belajar dan Keterampilan Berpikir Kritis Siswa pada Materi Sistem Peredaran Darah Manusia di SMA Negeri Trumon Kabupaten Aceh Selatan - Cut Kemalawati; Hasanuddin Hasanuddin; Khairil Khairil (Universitas Islam Negeri Ar-Raniry, 2018)
Metacognition skills enable students to develop into independent learners because they are the managers and assessors of their own thinking and learning. The purpose of this study was to determine the effect of metacognition strategies on learning outcomes and students' critical thinking skills on the subject of human circulatory system in SMA Negeri Trumon, South Aceh Regency. The method used in this study was True Experimentation with the form of Pretest-Posttest Control Group Design. The sample selection was conducted by random sampling. The population in this study were 223 students with a sample size 150. Data collection techniques on learning outcomes and critical thinking skills were carried out by providing pre-tests and post-tests in the form of objective tests. The learning outcomes and critical thinking skills was analyzed using N-Gain. N-Gain value for learning outcomes in experimental class (67,16) > N-Gain control class (51,57). The conclusion of this study is that the metacognition strategy influences the learning outcomes and critical thinking skills of students on the human circulatory system subject at SMAN Trumon, South Aceh District.